ACADEMICIAN N.A. LOGATCHEV AND HIS SCIENTIFIC SCHOOL: CONTRUBITION TO STUDIES OF THE CENOZOIC CONTINENTAL RIFTING - Sergey V. Rasskazov; Semen I. Sherman; Kirill G. Levi; Valery V. Ruzhich; Vladimir M. Kozhevnikov; Vladimir A. San’kov (Геодинамика и тектонофизика, 2015)
N.A. Florensov and N.A. Logatchev pioneered development of fundamental concepts of the structure and evolution of the Baikal system of rift basins. At the turn to the 21st century, in view of the wide availability of scientific research data on the Cenozoic continental rift zones located in Eurasia, Africa and North America, and taking into account the application of new research methods and options to process and analyze huge amounts of geological and geophysical data, a priority was comprehensive modeling of rifting from its origin to the current period of time. This scientific challenge was addressed by the research team under the leadership of N.A. Logachev.